2020
DOI: 10.1111/eci.13321
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐parametric system for risk stratification in mitral regurgitation: A multi‐task Gaussian prediction approach

Abstract: Background: We hypothesized that a multi-parametric approach incorporating medical comorbidity information, electrocardiographic P-wave indices, echocardiographic assessment, neutrophil-to-lymphocyte ratio (NLR) and prognostic nutritional index (PNI) calculated from laboratory data can improve risk stratification in mitral regurgitation (MR). Methods: Patients diagnosed with mitral regurgitation between 1 March 2005 and 30 October 2018 from a single centre were retrospectively analysed. Outcomes analysed were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Classification of HF into those with reduced, midrange, and preserved ejection fraction is important, 7 and risk stratification strategies depend partly on the behaviour of LVEF 8 , 9 and require a multi‐parametric approach. 10 , 11 , 12 , 13 LVEF may recover, remain stable, or decline owing to a complex interaction between comorbidities, frailty status, 14 , 15 , 16 , 17 , 18 , 19 medical or device treatment, 20 and disease progression. Our results are consistent with the results of other studies; compared with persistent HFrEF, subjects with HFrecEF are younger, with a higher prevalence of hypertension, lower prevalence of coronary artery disease, cerebrovascular disease, and diabetes mellitus, 3 , 21 and had higher interventricular septal thickness, lower left ventricular diameter, and a better biomarker indicator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Classification of HF into those with reduced, midrange, and preserved ejection fraction is important, 7 and risk stratification strategies depend partly on the behaviour of LVEF 8 , 9 and require a multi‐parametric approach. 10 , 11 , 12 , 13 LVEF may recover, remain stable, or decline owing to a complex interaction between comorbidities, frailty status, 14 , 15 , 16 , 17 , 18 , 19 medical or device treatment, 20 and disease progression. Our results are consistent with the results of other studies; compared with persistent HFrEF, subjects with HFrecEF are younger, with a higher prevalence of hypertension, lower prevalence of coronary artery disease, cerebrovascular disease, and diabetes mellitus, 3 , 21 and had higher interventricular septal thickness, lower left ventricular diameter, and a better biomarker indicator.…”
Section: Discussionmentioning
confidence: 99%
“…Classification of HF into those with reduced, midrange, and preserved ejection fraction is important, 7 and risk stratification strategies depend partly on the behaviour of LVEF 8,9 and require a multi‐parametric approach 10–13 . LVEF may recover, remain stable, or decline owing to a complex interaction between comorbidities, frailty status, 14–19 medical or device treatment, 20 and disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…35 In this study, NLR was found to predict all-cause mortality in our cohort of HF patients with LVEF ≤ 45%. NLR can also predict adverse outcomes in other cardiac diseases such as mitral regurgitation 36 and aortic stenosis. 37 Moreover, poor nutrition leads to impaired immune responses and leads to adverse outcomes in HF.…”
Section: Inflammatory and Nutrition Indicesmentioning
confidence: 99%
“…Currently, there is yet a multi-parametric approach in the risk stratification of MR. Recently, we reported that risk stratification of MR can be significant improved with the use of a multi-task Gaussian process learning model which outperformed logistic regression [17]. In this study, we extend previous analyses by assessing the comparative performance of several machine learning models, such as Decision Tree (DT), Random Forest (RF), Support Vector Machine (SVM), Artificial Neural Network (ANN), and Gradient Boosting Machine (GBM).…”
Section: Introductionmentioning
confidence: 76%